2020
DOI: 10.3390/life10080145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Single Session of Tai Chi Chuan Practice on Glucose and Lipid Metabolism and Related Hormones

Abstract: Background: To examine the effect of Tai Chi Chuan (TCC) practice on glucose and lipid metabolism and related hormones in TCC practitioners. Methods: Twenty-one TCC practitioners and nineteen healthy controls were included in this study. Classical Yang’s TCC was practiced by the TCC practitioners. The percentage changes in serum total cholesterol (TC), high-density lipoprotein-cholesterol (HDL-C), serum glucose (SG), serum insulin, serum insulin level, homeostatic model assessment of insulin resistance (HOMA-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…At the same time, the exercise intensity is moderate, which is favored by the middle-aged and elderly. Tai Chi has been shown to improve the level of blood glucose and lipid in diabetic patients, and the potential mechanism may be driven by insulin resistance, and reduction in inflammatory factors ( 16 , 17 ). Studies have found that Tai Chi can stimulate innate and adaptive immune cell responses and regulate inflammatory biomarkers, enhancing participants’ immune system function ( 5 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the exercise intensity is moderate, which is favored by the middle-aged and elderly. Tai Chi has been shown to improve the level of blood glucose and lipid in diabetic patients, and the potential mechanism may be driven by insulin resistance, and reduction in inflammatory factors ( 16 , 17 ). Studies have found that Tai Chi can stimulate innate and adaptive immune cell responses and regulate inflammatory biomarkers, enhancing participants’ immune system function ( 5 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…I wanted to see if I could find additional medical studies that were written in a more professional style and that were aimed at professionals, so I went to the PubMed database [113] and conducted a search for studies that included both cholesterol and tai chi in either the title or abstract. I found several such studies, a sampling of which are listed in the reference section [114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129]. Medical professionals who want to find medical studies on cholesterol that have involved qigong or Chinese herbal medicine can conduct similar searches.…”
Section: Author Commentmentioning
confidence: 99%
“…Clearly there are also studies in which, due to the objectives or specialism of the authors, focus on the parameters of a single discipline. This Special Issue reflects this, with some studies focused only on physiological parameters [16][17][18][19], and others on biomechanical parameters [20][21][22][23][24]. However, being aware that multidisciplinarity enriches scientific work [25], we have sought to emphasize this holistic approach in this special issue.…”
mentioning
confidence: 99%